Simulation study on crack extension law of asphalt pavement under temperature effect - Xie, Jing; Xu, Hui; Huang, Tuo (Frontiers in Built Environment, 2024)
In modern highway construction, asphalt pavement is a widely used structural form, which is easily affected by various external conditions, among which the temperature effect is the most significant. In this paper, the cohesion model is used to simulate the structural cracks of asphalt pavement, the finite element method is used to simulate the asphalt concrete pavement model, and the temperature field simulation model of the pavement is established by using ABAQUS software, with the help of which the spatial distribution of stresses under different temperature conditions is deeply explored, and then the crack extension law during the process of temperature change is systematically investigated, and the effect of the temperature load on the degree of damage to the asphalt pavement is also studied. With the temperature change, the pavement surface layer is affected the most, and the soil base layer is affected the least. The higher the external temperature, the larger the crack expansion width inside the pavement structure, and the faster the corresponding expansion rate. The fatigue damage rate of the pavement structure is accelerated along with the increase of temperature. The research results can provide a theoretical basis for improving the high temperature performance of asphalt pavement.